The EXCEL Trial: The Surgeons’ Perspective - Marjan Jahangiri (Radcliffe Medical Media, 2020)
There have been several investigations comparing the efficacy of percutaneous coronary intervention and coronary artery bypass grafting surgery for treatment of left main stem disease. This includes the Evaluation of XIENCE versus Coronary Artery Bypass Graft Surgery for Effectiveness of Left Main Revascularizaton (EXCEL) trial, which has garnered significant controversy surrounding its experimental design and reporting of its results. The authors review the methodology, results, caveats and statements on the EXCEL trial. They also review the other trials in the management of left main stem disease comparing percutaneous coronary intervention with coronary artery bypass grafting, as well as the SYNTAX score and its role in future guidelines for revascularisation. These findings have significant implications for current practice, influencing the growing role for multidisciplinary team meeting and allowing clinicians and patients to make the right choice.